Butyryl/Caproyl-CoA:Acetate CoA-transferase: cloning, expression and characterization of the key enzyme involved in medium-chain fatty acid biosynthesis. Issue 8 (27th August 2021) - Yang, Qingzhuoma; Guo, Shengtao; Lu, Qi; Tao, Yong; Zheng, Decong; Zhou, Qinmao; Liu, Jun
Abstract: Coenzyme A transferases (CoATs) are important enzymes involved in carbon chain elongation, contributing to medium-chain fatty acid (MCFA) biosynthesis. For example, butyryl-CoA:acetate CoA transferase (BCoAT) is responsible for the final step of butyrate synthesis from butyryl-CoA. However, little is known about caproyl-CoA:acetate CoA-transferase (CCoAT), which is responsible for the final step of caproate synthesis from caproyl-CoA. In the present study, two CoAT genes from Ruminococcaceae bacterium CPB6 and Clostridium tyrobutyricum BEY8 were identified by gene cloning and expression analysis. Enzyme assays and kinetic studies were carried out using butyryl-CoA or caproyl-CoA as the substrate. CPB6-CoAT can catalyze the conversion of both butyryl-CoA into butyrate and caproyl-CoA into caproate, but its catalytic efficiency with caproyl-CoA as the substrate was 3.8-times higher than that with butyryl-CoA. In contrast, BEY8-CoAT had only BCoAT activity, not CCoAT activity. This demonstrated the existence of a specific CCoAT involved in chain elongation via the reverse β-oxidation pathway. Comparative bioinformatics analysis showed the presence of a highly conserved motif (GGQXDFXXGAXX) in CoATs, which is predicted to be the active center. Single point mutations in the conserved motif of CPB6-CoAT (Asp 346 and Ala 351 ) led to marked decreases in the activity for butyryl-CoA and caproyl-CoA, indicating that the conserved motif is the active center of CPB6-CoAT and that Asp 346 and Ala 351 have a significant impact on the enzymatic activity. This work provides insight into the function of CCoAT in caproic acid biosynthesis and improves understanding of the chain elongation pathway for MCFA production.